Effect of galectin-3 and brain natriuretic peptide levels on echocardiographic parameters of left heart chamber following coronary artery bypass grafting - Yulia A. Styazhkina; Irina F. Grishina; Nina B. Poletaeva; Tatyana F. Peretolchina; Olga V. Nikolaenko (КардиоСоматика)
BACKGROUND: The article analyzes changes of echocardiographic (EchoCG) parameters of the left chamber over time and their relationship with galectin-3 and NT-proBNP levels in patients with coronary artery disease (CAD) following coronary artery bypass grafting (CABG) and various recovery periods.